Fenomenologis Penerapan Akuntansi Dalam Rumah Tangga Pada Guru-Guru SMK Publik Makassar - Nurlaila Hasmi (Tangible Journal, 2019)
Every family has family financial management & acts as a manager, how each family will manage finances will be different, and usually the family finances will be fully regulated by the Housewife (wife). This research tries to reveal the role of teachers in Makassar Public Vocational School on how informants apply household accounting and manage their finances in the household on 4 (four) important things, namely: budgeting, recording, decision making and long-term planning. This study provides findings from a phenomenological study of accounting in the household. This study aims to uncover family financial planning oriented to explore financial management in the families of teachers in Makassar Public Vocational Schools. The focus of discussion and observation is sought to answer the problem of teachers' understanding of the budget in family financial planning. The qualitative method used in this research uses the theoretical basis for the study of phenomenology. The results of the study it can be concluded that the importance of the role of accounting in the household to be able to plan every budget in the household, recording, decision making and long-term planning in the household. This will have a very good impact on controlling the financial cycle and to avoid misunderstandings between husband and wife, as well as the need for long-term decision making and planning in managing family finances better and more precisely.